2020
DOI: 10.34306/att.v2i1.74
|View full text |Cite
|
Sign up to set email alerts
|

Application of Blockchain Technology in e-LoA Technopreneurship Journal

Abstract: LoA or Letter of Acceptance is a statement received. LoA is usually used as a statement of scholarship acceptance or even journal acceptance. In addition, the current issuance of LoA is still conventional, using paper as the access medium. This is certainly inefficient. In addition, the issuance of LoAs that can be accessed through the website also has certain problems. Many parties doubt the security of the LoA issued through the website, whether confidentiality is really maintained or not. To solve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
0
16
0
5
Order By: Relevance
“…After discussion with several faculty members [36], we have found that it is not feasible for a faculty member to strike a balance between teaching and other commitments, as already mentioned. While making balance, faculty creates a lot of stress, which affects teaching performance, severely affecting results [37].…”
Section: Impact Of Excessive Pressure On Faculty Performancementioning
confidence: 82%
“…After discussion with several faculty members [36], we have found that it is not feasible for a faculty member to strike a balance between teaching and other commitments, as already mentioned. While making balance, faculty creates a lot of stress, which affects teaching performance, severely affecting results [37].…”
Section: Impact Of Excessive Pressure On Faculty Performancementioning
confidence: 82%
“…On the Start Page or picture 2, you can see that there are 4 buttons namely the Login, Register, Register and Exit Register buttons. The Login button functions to go to the Main Menu page, the Register button functions to register as a user to be able to Login, the Exit button functions to exit the game [26] [27].…”
Section: Figure 3 Use Case Services Worker Diagrammentioning
confidence: 99%
“…As the eminent physicist Paul Davies believed, the designer assumption is much more economical than the multiverse assumption. To control for the invisible infinite science of technology just to explain what seems like an extreme case of excess baggage carry [32].…”
Section: The Role Of Islam Implements Metaphysical Principles In Scie...mentioning
confidence: 99%